The interrelationship between anti‐Müllerian hormone, ovarian follicular populations and age in mares. (29th September 2014) - Claes, A.; Ball, B. A.; Scoggin, K. E.; Esteller‐Vico, A.; Kalmar, J. J.; Conley, A. J.; Squires, E. L.; Troedsson, M. H. T.
Summary Reasons for performing study Anti‐Müllerian hormone (AMH) is a granulosa‐cell‐derived glycoprotein, which plays an important inhibitory role during folliculogenesis. Concentrations of AMH are highly correlated with antral follicle counts (AFCs) in other species, which in turn are related to follicular reserve. Relatively little is known about AMH and AFC in the mare. Objectives To determine plasma AMH concentrations and AFCs in mares of different ages, to measure the repeatability of AMH concentrations and AFCs within and across oestrous cycles and to assess the relationship between plasma AMH concentrations and AFCs with regard to mare age and follicle size. Study design An observational study examining the relationship between AMH, AFC and age in 45 mares. Methods Young (3–8 years), middle‐aged (9–18 years) and old mares (19–27 years) were examined by transrectal ultrasonography over 2 or 3 oestrous cycles. Plasma AMH concentrations and AFCs were determined, and antral follicles were classified by size into different groups. Results Plasma AMH concentrations varied widely between mares within similar age groups. Antral follicle counts were significantly lower in old mares than in young and middle‐aged mares, and AMH concentrations were significantly lower in old than in middle‐aged mares. A positive relationship was detected between AFC and AMH, and this relationship varied by mare age with a strong correlation in older mares (ρ = 0.86; P<0.0001), a moderate correlation in middle‐aged mares (ρ = 0.60; P = 0.01) and no correlation in young mares (ρ = 0.40, P<0.4). The AMH concentrations were significantly related to the number of antral follicles between 6 and 20 mm in diameter, and the repeatability of AFCs and AMH concentrations was high within and between oestrous cycles. Conclusions Our findings indicate that the relationship between AMH and AFC varies across age groups, and concentrations of AMH might be a better reflection of reproductive age than calendar age.